Pemikiran Majelis Zikir Hasan Ma’shum tentang Tasawuf dan Responsnya terhadap Dunia Postmodern - Moh. Syihabuddin (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2018)
The article attempts to describe the thought of Hasan Ma'shum's followers on Sufism along with their responses to the Postmodern world. Employing Bourdieu's genetic structuralism analysis theory, the author creates a frame work analysis to reveal the phenomenon. This is a part of critical theories in Sociology which has been developed to overcome the problem of dichotomy between individual and society, agent and social structure, and freedom vis a vis determinism. The study finds that the followers of him are able to wisely respond to the Postmodern culture, which massively spread and unstoppably influence many aspects of social realms, without necessarily overreact and behave radically. Cultural capital, which shapes Hasan's thought and views as the agent of sufism, has been a sort of habituation of their life to live as homo socious (social beings) and religious community. The cultural capital has generated a habitus within their selves and enabled them to gain knowledge of Sufism, and at the same time led them to wisely respond to the Postmodern reality.